Genetic Analysis of Oil and its Impact in Selection of High Yielding Genotypes in Safflower (Carthamus tinctorius L.) - Gupta, R K; Singh, S P (Annals of Arid Zone, 2016)
The present study based on 6 generation means of 5 parents half diallel in Safflower (Caarthamus tinctorius L.) was conducted to study the nature of gene action for test weight and oil percentage. Scaling test was significant for all crosses indicating the presence of non allelic interaction except ’EC 33969’ X ’Local’ for oil percentage. Three crosses for test weight and 5 crosses for oil percentage showed significant additive gene effect (d)while only’EC27510’ X’Local’ (3.08) for test weight and ’EC31367’ X ’EC27249’ (17.11) for oil percentage had significant positive dominance effect (h). The sign of dominance (h) and dominance x dominance (I) indicated complementary epistasis for two crosses for test weight and 3 crosses for oil percentage.